The The Impact of Environmental, Social, and Governance (ESG) on Financial Performance Moderated by Firm Age and Firm Size - Ibrahim Ibrahim; Fazli Syam BZ; Nadirsyah Nadirsyah (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study investigates the relationship between Environmental, Social, and Governance (ESG) disclosure and corporate financial performance, with firm age and firm size incorporated as moderating factors. ESG disclosure has increasingly been recognized as an important indicator of firms’ commitment to sustainability and responsible business conduct. Financial performance is assessed through Tobin’s Q, Return on Assets (ROA), and Return on Equity (ROE). The study examines consumer goods firms listed on the Indonesia Stock Exchange over a five-year horizon using Moderated Regression Analysis (MRA). The findings indicate that firm age and firm size play important roles in conditioning the relationship between ESG disclosure and financial performance, suggesting that the impact of ESG disclosure differs depending on firm-specific attributes.